EFFECT OF WATER EXTRACT OF ALOE VERA ON GERMINATION AND EARLY GROWTH OF DIANTHUS BARBATUS - Svjetlana Zeljković; Lidija Milojević; Emina Mladenović; Margarita Davitkovska; Zvezda Bogevska (Ss Cyril and Methodius University in Skopje, Faculty of Agricultural Sciences and Food - Skopje, 2022)
The Sweet William - Dianthus barbatus (L.) is a plant from Caryophyllaceae family. The germination and growth of the plant are important phenological stages, and plant survival depends on them. The seed that has better germination energy also has better vigor, so it is more resistant to stressful conditions during germination. The aim of this study was to examine the possibilities and effectiveness of water extracts of plant species Aloe vera on the seed germination and early growth of Sweet William seedlings - Dianthus barbatus (L.). The experiment was conducted in laboratory conditions at the Faculty of Agriculture, University of Banja Luka and consisted of control (distilled water) and treatment with water extract of Aloe vera. Water extracts were prepared from fresh leaves and experiments were conducted in Petri dishes at 5, 10, and 15%. The temperature in the laboratory was constant at 20°C and the light regime was set to 16h day/8h night. Water extracts of Aloe vera at a concentration of 5% had a positive effect on the seed germination and germination energy, while a concentration of 15% had a positive effect on shoot and root length, and fresh mass of Dianthus barbatus seedlings.
Keywords: Aloe extract, germination energy, Sweet William